EXPLORING ENGLISH VOCABULARY GROWTH THROUGH ISLAMIC SONGS EARLY CHILDHOOD EDUCATION - Muhammad Rafi'i (Linguistik : Jurnal Bahasa dan Sastra, 2026)
This study investigates how Islamic song-based instruction shapes the development of English vocabulary among Muslim preschool children through a qualitative case study approach. Recognizing the critical role of early childhood as a formative stage for both language acquisition and identity construction, this research integrates Krashen’s Affective Filter Hypothesis, Vygotsky’s Sociocultural Theory, and music cognition frameworks to understand how culturally resonant songs influence learning. Data were collected over an eight-week period in two Islamic preschools, involving sustained classroom observations, semi-structured teacher interviews, and analysis of teaching materials and song lyrics. Thematic analysis identified three overarching patterns: (1) Islamic songs fostered a positive and anxiety-free emotional climate, (2) they stimulated spontaneous and meaningful use of English vocabulary during and beyond classroom activities, and (3) they reinforced children’s cultural and religious identity while simultaneously promoting linguistic growth. These findings underscore the pedagogical potential of faith-integrated musical practices, demonstrating that Islamic songs not only enhance vocabulary acquisition but also cultivate holistic learning experiences that respect the cultural context of young learners. Implications are discussed for early childhood educators, curriculum designers, and policymakers seeking culturally responsive and engaging approaches to English language education.